5.8 GHz wireless localization based weighted algorithm for home network applications - Mankong, Thanadon; Maw, Myo Myint; Promwong, Sathaporn (My University, 2020)
New wireless network solution, the distributed network nodes short range area are unknown. This paper, consider the accuracy with weighted algorithm (WA) based on wireless network received signal strength is evaluated for localization. The wireless transmission model using wireless ISM band with four reference nodes and one target node operated at frequency of 5.8 GHz. Distance error is used to evaluate the precision of location approximation with respected to the CDF. The received signal strength in measurement field is presented in this paper. The contributes of this paper is useful for a study in an indoor positioning with 5.8 GHz for future home network applications.
Keywords: Component; Indoor localization; Received signal strength; Weighted algorithm; Wireless localization; Wireless sensor network